2005
DOI: 10.1093/annonc/mdi254
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant docetaxel followed by adjuvant doxorubicin and cyclophosphamide in patients with stage III breast cancer

Abstract: Background: To evaluate clinical and pathologic response to neoadjuvant docetaxel therapy in patients with stage III breast cancer. Patients and methods: Forty-five patients were planned to receive four cycles of docetaxel 100 mg/m 2 every 3 weeks, followed by surgery, four cycles of doxorubicin 60 mg/m 2 and cyclophosphamide 600 mg/m 2 (AC) every 3 weeks, radiation therapy (RT), and tamoxifen when indicated.Results: After four cycles of neoadjuvant docetaxel, the clinical response rate within the breast was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
4
23
0
1
Order By: Relevance
“…The few neoadjuvant studies conducted to-date with single agent doxorubicin or docetaxel reported a very similar activity [23][24][25]. In our trial, ER negative status was a strong but unspecific predictor of sensitivy to either docetaxel and doxorubicine.…”
Section: Discussionsupporting
confidence: 60%
“…The few neoadjuvant studies conducted to-date with single agent doxorubicin or docetaxel reported a very similar activity [23][24][25]. In our trial, ER negative status was a strong but unspecific predictor of sensitivy to either docetaxel and doxorubicine.…”
Section: Discussionsupporting
confidence: 60%
“…However the report confirms that in this subgroup of patients, primary endocrine therapy has excellent survival outcome compared to other approaches of treatment i.e. multimodal treatment using chemotherapy (60-80% overall 5 year survival) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 71%
“…[27][28][29][30][31]. Ixabepilone has a similar, but distinct, mechanism of action to that of taxanes and appears to be less sensitive to mechanisms that confer taxane resistance (32,33).…”
Section: Introductionmentioning
confidence: 99%